2015
DOI: 10.1088/1674-4527/15/2/009
|View full text |Cite
|
Sign up to set email alerts
|

Chromospheric activity in several single late-type stars

Abstract: New high-resolution echelle spectra of six single late-type Pleiades-like stars (V368 Cep, EP Eri, DX Leo, GJ 211, PW And and V383 Lac) were obtained with the 2.16 meter telescope at Xinglong Station in 2008-2010. Using the spectral subtraction technique, we analyzed our spectroscopic data and calculated the equivalent widths of excess emission from several indicators of chromospheric activity (Na I D 1 , D 2 , Hα and Ca II infrared triplet lines). All our results using chromospheric activity indicators confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 88 publications
(148 reference statements)
3
13
0
Order By: Relevance
“…Chromospherically active stars and their properties have been studied previously by many authors (Strassmeier et al 1990(Strassmeier et al , 1993Doyle et al 1994;Fekel et al 2005;Montes et al 2004;Hall 2008;Biazzo et al 2009;Frasca et al 2010;Cao & Gu 2015;Zhang et al 2015;etc). The spectral subtraction technique has been widely applied to different chromospheric activity indicators (Barden 1985;Montes et al 2004;Zhang et al 2015;etc).…”
Section: Introductionmentioning
confidence: 98%
“…Chromospherically active stars and their properties have been studied previously by many authors (Strassmeier et al 1990(Strassmeier et al , 1993Doyle et al 1994;Fekel et al 2005;Montes et al 2004;Hall 2008;Biazzo et al 2009;Frasca et al 2010;Cao & Gu 2015;Zhang et al 2015;etc). The spectral subtraction technique has been widely applied to different chromospheric activity indicators (Barden 1985;Montes et al 2004;Zhang et al 2015;etc).…”
Section: Introductionmentioning
confidence: 98%
“…Optical wavelength observations in previous researches also show that the intensities of Hα and Hβ are enhanced during the flares of EV Lac (Melikian et al, 2006;Honda et al, 2018). The enhancements of the Balmer lines indicate that the chromospheric activities of the flare stars occur in the middle chromosphere (Montes et al, 2000;Zhang, 2011;Zhang et al, 2015). In addition to the Balmer lines, several studies have shown that Ca II H & K, Na I D and He I lines also exhibit enhanced radiation during flares (Lalitha et al, 2013;Kowalski et al, 2013Kowalski et al, , 2016.…”
Section: Discussionmentioning
confidence: 91%
“…They found EW 8542 /EW 8498 ratios of 1.0-1.7, which implies the presence of optically thick plages. This is typical of many late-type stars [111,[122][123][124][125][126]. The infrared triplet lines are formed in the lower chromosphere through subordinate transitions between the excited levels of Ca II 4 2 P 1/2,2/3 and meta-stable 3 2 D 3/2,5/2 [127,128].…”
Section: Spectroscopic Diagnosticsmentioning
confidence: 98%
“…Magnetic activity is also evidenced, in some cases, in the form of X-ray variability associated with magnetised coronae [266], transition region emission or flares at optical, X-ray, UV and radio wavelengths [113,126,163,266,[273][274][275]. Note that the photometric and spectroscopic characteristics of FK Comae stars closely resemble those of RS CVn stars, although the former are single, rapidly rotating giant stars that do not show any evidence of multiplicity.…”
Section: Rs Canum Venaticorum Systemsmentioning
confidence: 99%